Effect of commercially-available yogurts on streptococcus mutans - Barrientos, Aviane Chakri B.
Introduction. Probiotics, such as Lactobacillus bulgaricus and Streptococcus thermophilus used as yogurt starter cultures, have been successfully used to control gastro-intestinal diseases and according to studies (Stamatova et al., 2009; Bonifait et al., 2009), these may exert beneficial effects in the oral cavity by inhibiting cariogenic streptocicci (Bushan et al., 2010) and periodontopathogenic bacteria. Lactic acid bacteria can produce different antimicrobial components (Yesilik et al., 2011) which may also benefit the oral microflora. However, data is still sparse on the probiotic action in the oral cavity. The purpose of the study was to determine the antimicrobial activity of commercially-available yogurts against S. mutans. It also aimed to determine the changes in yogurt's pH in time.